A randomized phase II study on the effects of 5-Aza-2'-deoxycytidine combined with either amsacrine or idarubicin in patients with relapsed acute leukemia: an EORTC Leukemia Cooperative Group phase II study (06893) - Willemzen, Rein; Suciu, S.; Archimbaud, E.; Muus, P.; Stryckmans, P.; Louwagie, E. A.; Berneman, Z.; Tjean, M.; Wijermans, P.; Döhner, Hartmut; Jehn, U.; Labar, B.; et al. (Leukemia, 1997)
5-Aza-2′-deoxycytidine combined with either amsacrine or idarubicin has been applied in a treatment protocol for patients with a relapse of acute myeloid or lymphocytic leukemia. Sixty-three patients received 5-Aza-2′-deoxycytidine 125 mg/m² as a 6 h infusion every 12 h for 6 days in combination with either amsacrine 120 mg/m² as a 1 h infusion on days 6 and 7 (n = 30) or idarubicin 12 mg/m² as a 15 mm infusion on days 5, 6 and 7 (n = 33). Twenty-three patients (36.5%) obtained a complete remission (CR); eight of 30 patients treated with amsacrine and 15 of 33 treated with idarubicin. Patients with an interval of more than 1 year between initial diagnosis and start of the protocol achieved CR in 51.4%, compared to 15.4% for patients with an interval of less than 1 year. Patients with normal cytogenetics had a higher CR rate (61%) than those with abnormal cytogenetic findings (15.8%). Digestive tract and hematologic toxicity was prolonged, compared to standard induction schedules. Median disease-free survival was approximately 8 months, with only 20% of patients staying in remission for more than 1 year. 5-Aza-2′-deoxycytidine is a good antileukernic agent with considerable toxicity. Current results merit further investigations in previously untreated leukemia.
Gesehen am 31.10.2024